Social capital, political connections, and household enterprises: Evidence from Vietnam - Christina Kinghan; Carol Newman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Social capital and political connections can play an important role in developing countries where markets fail and institutions are weak. This paper explores their role in household micro-enterprise operation and success in the rural low-income setting of Vietnam. We propose that social capital and political connections assist households in accessing resources necessary to establish and operate an enterprise. Using three waves of panel data on a large sample of households surveyed between 2008 and 2012 we find strong evidence to suggest that both are important in assisting enterprise operation, particularly for the poorest households. Their role in determining the success of an enterprise is less clear with the evidence suggesting that conditional on enterprise formation physical inputs play a more important role.
Keywords: D13; O12; O17; 330; social capital; political connections; household enterprises; Vietnam